An evaluation of the performance through the comparison of kinematic variables for the official records in world women`s triple jumper - Ryu, J.-K.; Kim, G.-T. (Korean Journal of Sport Science, 2021)
Purpose: The purpose of this study was to examine the difference and consistency of kinematic variables for each athlete by selecting the official records of the world's elite female triple jumpers to evaluate the performance level. Methods: Three athletes who won the prizes at the World Championships Daegu 2011 Women's Triple Jump were selected as the study subjects, and only the successful trials were used for analysis. Pearson's correlation analysis was conducted with the kinematic variables in the hop, step, and jump phase, respectively. Also, kinematic variables with statistically significant correlations between braking time and pushing time and related variables were described separately. The duty factor and support factor for the hop, step, and jump of support phases were calculated. Results: The successful trials rate were 66.7% for Olha, 50% for Olga, and 83.3% for Caterine. In the last three stride distances of the approach run, Olha and Caterine had a "medium-long-short" pattern and Olga had a "long-short-medium" pattern. There was no difference in the duty factor value between hop and jump phases in the `hop-dominate` technique type, but there was a difference in the jump phase in the `balance` technique type, and the duty factor value in the step of both technique types was greater than that of hop and jump phases. As for the percentage of the support factor, Olha and Caterine had a characteristic that the percentage of braking time in step and jump phases was opposite. On the other hand, Olga had the same percentage for the hop and step phase, and a smaller percentage for the jump phase. Conclusion: To increase the accuracy of the board touch-down, maintain a certain last stride(1SL) depending on the technique type. This consistency of the approach run increases reduces distance loss on the take-off board and increases the successful rate of each trial. The duty factor can judge both the performance level and the technique type of triple jump, and the support factor is a variable that can classify the technique types of hop, step, and jump phases. If both the relative time required for the triple jump and the variability of the support time(braking and pushing) for each phase are constant, the difference in records by trial will be small.